PELAKSANAAN PEMBERDAYAAN PEMBINAAN DAN PENGAWASAN ORGANISASI KEMASYARAKATAN DI KABUPATEN LOMBOK TENGAH - SOFWAN, SOFWAN; JAYADI, HAERUMAN; BASNIWATI, AD; AMALIA, RISKA ARI (GANEC SWARA, 2023)
The government wants to foster and empower mass organizations by managing the activities of mass organizations not to take actions that are contrary to the sovereignty of the Unitary State of the Republic of Indonesia based on Pancasila and the 1945 Constitution of the Republic of Indonesia. The reality that occurs in the field is often inconsistent with the objectives of the law. law, for example regarding the problem of mass organizations in Central Lombok Regency which resulted in the formulation of the problem: 1) How is the legality of Community Organizations in Central Lombok Regency? 2) How is the implementation of empowerment, guidance and supervision of CBOs in Central Lombok Regency, 3) What are the obstacles faced by the Regional Government in implementing the empowerment, guidance and supervision of Community Organizations in Central Lombok Regency. The research method used is an empirical research method. The conclusions obtained are 1) CSOs in Central Lombok district have a legal basis because they have regulations as a legal basis and several CSOs have been registered with Bakesbangpol, 2) Empowerment, guidance and supervision of CSOs in Central Lombok Regency has been carried out by the local government by way of : Empowerment: through policy facilitation, strengthening institutional capacity, and improving the quality of human resources, Guidance: counseling, public consultation, and training, Supervision: supervision carried out by opening a complaint service for organizations that are indicated to be carrying out activities that are not in accordance with regulatory provisions legislation and granting and revoking permits for mass organizations. 3) The obstacles faced are as follows: a. There are still many CSOs that carry out activities outside the field of activity listed in the AD/ART, b) Many CSOs are reluctant to report their existence at Bakesbangpol Central Lombok Regency so they are not registered in the Ormas data, c) Addresses of secretariats and CSOs and Ormas management often changes.